Evaluation of Antioxidant and Oxidative Stress Activity of Carthamus tinctorius L. Extract in Lung Cancer A549 Cells - Alahmadi, Tahani Awad; Alharbi, Sulaiman Ali; Ravindran, Balasubramani; Saravanan, Karunakaran (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: C. tinctorius (safflower) natural food colorant and has been used to control high blood pressure, supress oxidation, cancer immunosuppressive drug, inhibits blood clots, dilate blood vessels, and as neuroprotective agents. Several investigations indicate the relationship between oxidative processes and emergence of cancer. The current investigation data confirms the antiproliferative activity of Safflower against A549 cancer cell line but little is known about their antioxidant mechanisms. Materials and Methods: Nitric Oxide (NO) and Lipid Peroxidation (LPO) levels were measured in order to explore the antioxidant properties of safflower extract. Lactate Dehydrogenase (LDH), reduced Glutathione (GSH), Superoxide Dismutase (SOD) and Catalase (CAT) were measured by UV-spectrophotometric analysis. Further, apoptotic key regulator BAX and SMAC gene expression were also analysed. Results: The dose-dependent antioxidant activity of Safflower extract induced apoptosis in A549 cells. There was significant increase in LPO, NO, LDH, SOD and CAT (*p < 0.0001) activities except GSH. Our data confirmed that safflower treated A549 cells inhibits the oxidation by scavenging free radicals and induced apoptosis by increased gene expression BAX and SMAC. Conclusion: The current findings indicates safflower extract might be potential alternative medicine for the treatment of lung cancer.
Keywords: Safflower; Antioxidant; Anti-cancer; Lipid Peroxidase; Nitric Oxide; Polymerase Chain Reaction